STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM IMPLEMENTASI KEBIJAKAN PENDIDIKAN INKLUSIF DI SMP NEGERI 2 YOGYAKARTA - Zahra Fadhilah Putri; Nauval Fauzan Miarakhman; Rimalia Dwi Krisnawati (Khazanah Intelektual, 2021)
AbstractEducation is an important thing in human life. The success of an educational institution is largely determined by the leadership role of the principal. The principal is required to be able to bring the school towards the achievement of predetermined goals. Currently, the city of Yogyakarta has established an inclusive school policy as contained in the Regulation of the Governor of the Special Region of Yogyakarta Number 21 of 2013 Article 3 concerning the Implementation of Inclusive Education as a form of equity and a form of education without discrimination. However, in reality this policy is not yet clearly known by school principals, so it requires appropriate leadership strategies in dealing with problems and managing good inclusive schools to improve school quality. One of them is SMPN 2 Yogyakarta, which transforms the regular school system into an inclusive school. Therefore, this study aims to identify and describe the issues of inclusive education faced by the principal of SMP Negeri 2 Yogyakarta as well as to describe the leadership strategy of the principal in overcoming issues of school principals in inclusive schools at SMPN 2 Yogyakarta. This research uses descriptive qualitative research with data collection methods using interview techniques, observation, and documentation. The achievements of SMPN 2 Yogyakarta after following the policy to turn schools into inclusive schools include: sports and journalism.